Metabolomic signatures of intestinal colonization resistance against Campylobacter jejuni in mice - Shayya, Nizar W.; Bandick, Rasmus; Busmann, Lia V.; Mousavi, Soraya; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2023)
Introduction Campylobacter jejuni stands out as one of the leading causes of bacterial enteritis. In contrast to humans, specific pathogen-free (SPF) laboratory mice display strict intestinal colonization resistance (CR) against C. jejuni, orchestrated by the specific murine intestinal microbiota, as shown by fecal microbiota transplantation (FMT) earlier. Methods Murine infection models, comprising SPF, SAB, hma, and mma mice were employed. FMT and microbiota depletion were confirmed by culture and culture-independent analyses. Targeted metabolome analyses of fecal samples provided insights into the associated metabolomic signatures. Results In comparison to hma mice, the murine intestinal microbiota of mma and SPF mice (with CR against C. jejuni) contained significantly elevated numbers of lactobacilli, and Mouse Intestinal Bacteroides, whereas numbers of enterobacteria, enterococci, and Clostridium coccoides group were reduced. Targeted metabolome analysis revealed that fecal samples from mice with CR contained increased levels of secondary bile acids and fatty acids with known antimicrobial activities, but reduced concentrations of amino acids essential for C. jejuni growth as compared to control animals without CR. Discussion The findings highlight the role of microbiota-mediated nutrient competition and antibacterial activities of intestinal metabolites in driving murine CR against C. jejuni. The study underscores the complex dynamics of host-microbiota-pathogen interactions and sets the stage for further investigations into the mechanisms driving CR against enteric infections.